Designing with the mind in mind : simple guide to understanding user interface design rules - Johnson, Jeff (Consultant) (Morgan Kaufmann Publishers/Elsevier, 2010)
"Interface designers and developers, software designers, web designers, web application designers, interaction designers, appliance designers and developers, information architects, usability engineers, usability evaluators and development managers, students and teachers in computer science, graphic design, HCI, and usability."--Resource description page